Complete Denture - Border Molding Technique Using a Laboratory Condensation Silicone Putty: Review - Melo Neto, Clóvis Lamartine de Moraes; Dos Santos, Daniela Micheline; Goiato, Marcelo Coelho (Prague medical report, 2023)
During the fabrication of a complete denture, functional impression is taken. Literature studies show that polydimethylsiloxane (condensation silicone) has not been reported by United States dental schools to perform border molding. Thus, the purpose of this article is to review the functional impression technique when border molding is performed with a laboratory condensation silicone putty.
Keywords: silikony; Complete denture; Denture, Complete; Dental impression technique; celkové zubní protézy; Humans; Polydimethylsiloxanes; Border moulding; Silicone elastomers; Silicones; lidé